Cognitive Restructuring untuk Mengurangi Kenakalan Peserta Didik MTs - Ahsaniatil Muawanah; Asrowi Asrowi; Agus Tri Susilo (Jurnal Psikoedukasi dan Konseling)
Abstract: This study aims to examine the effectiveness of cognitive restructuring in reducing juvenile delinquency in MTs students. This research is a quasi-experimental with an experimental design in the form of a Non-Equivalent Control Group Design. The subjects of this study were students, totaling 52 students. Sources of data are students. Data collection techniques in this study used a questionnaire. The data analysis technique used the independent sample t-test formula by comparing the averages of the two groups, namely the experimental group and the control group. The test results on the pretest scores of the experimental group and the control group obtained equivalent results. The test results on the experimental and control groups' post-test scores obtained significant results. Thus there is a difference after the treatment of cognitive restructuring. It shows that there is a significant difference between the control group and the experimental group. With this research, it can be concluded that it effectively reduces student delinquency. Based on these results, it is hoped that it will become a reference for implementing Guidance and Counseling services in helping students concerning cognitive restructuring and juvenile delinquency.